Emerging regional innovation policies for industry 4.0: analyzing the digital innovation hub program in European regions (2020)
urpose: Industry 4.0 or digitization, from a regional innovation system (RIS) and policy perspective to improve regional innovation, is over-looked. Specifically, this paper aims to focus on analyzing the nascent European Commission (EC) digital innovation hub (DIH) program, designed for fostering transition into Industry 4.0 in regions and facilitating new path development. Design/methodology/approach: Empirically, 10 Spanish DIH is explored through interviews and secondary data analysis. Findings: The results suggest that DIHs despite their emerging and trial-and-error stage are designed for promoting multi-actor collaborative platforms including non-local actors to stimulate transition into Industry 4.0 by promoting place-based collaboration alliances that respond to local/regional contextual specificities and demands. These regional-based platforms facilitate public-private partnerships that co-design policy initiatives resulting from co-participation and negotiation of spatially-bounded oriented initiatives for digitizing. Originality/value: The authors answer: what are the key characteristics of emerging European-level regional innovation policies aimed at facilitating Industry 4.0 in regions? This is the first study on the topic.